INTEGRATING LASER TECHNOLOGY INTO DERMATOLOGY EDUCATION: EFFICACY, SAFETY, AND COMPTENCY-BASED TRAINING: A NARRATIVE REVIEW - Wiktorowicz, Justyna Maria; Sinczak, Zofia; Kowalska, Anna Maria; Bulińska, Nicole; Sobol, Aleksandra Zofia; Kuls, Aleksandra Anna; Pabis, Bogusław; Kadłubańska, Martyna; Zembrzuska , Sonia; Bajerski, Stanisław (International Journal of Innovative Technologies in Social Science, 2026)
The rapid advancement of laser technologies has significantly transformed contemporary dermato-logical practice, creating a growing demand for structured and competency-based education in this field. Despite the widespread clinical application of laser systems, variability in training standards and limited integration of modern educational technologies remain persistent challenges with impli-cations for both patient safety and healthcare systems.This review aims to examine the integration of laser technology into dermatology education, with a particular focus on treatment efficacy, safety considerations, and the role of technology-enhanced learning in improving clinical competency. A narrative review of recent literature was conducted, focusing on studies related to laser applications in dermatology, associated clinical outcomes, and emerging educational approaches, including simulation-based training, e-learning platforms, and virtual or augmented reality tools.The findings indicate that while laser therapies demonstrate high clinical efficacy, their safe and effective use is strongly dependent on practitioner expertise and the quality of training. Current educational models remain heterogeneous and often lack standardized competency frameworks, contributing to disparities in skill acquisition and access to high-quality training. Technology-enhanced, competency-based approaches show considerable potential in addressing these gaps by improving procedural proficiency, supporting continuous learning, and enhancing patient safety outcomes.The review highlights the need for the development of standardized, technology-integrated training frameworks that align with the evolving demands of dermatological practice. It also emphasizes broader implications for healthcare education systems, including the need to ensure equitable access to advanced training and to support lifelong learning in rapidly changing clinical environments.